Analysis of wave processes in an underground gas pipeline (mathematical model and field experiment). (October 2021) - Glot, I.; Shardakov, I.; Shestakov, A.; Tsvetkov, R.
Highlights: Analyzed the mechanical state of underground gas pipeline filled with gas. Simulation: deformation waves caused by the impacts on pipe, soil and gas. Field tests: vibration response to the impacts on pipe, soil and pressure surges. Low-frequency vibrations caused by pressure surges are recorded at 2 km. Vibrations caused by impacts on pipe and ground propagate no further than 60m. Abstract: The paper studies the propagation of deformation waves in an underground gas pipeline. Deformation process occurring in the pipeline is caused by the interaction of the gas pumped through the pipe, the metal walls of the pipe and the soil surrounding the pipeline. Vibration processes in the pipeline caused by various mechanical impacts on the pipe and gas are investigated. The paper presents the results of numerical experiments and field tests carried out on the underground section of the operating main gas pipeline. The numerical simulation of dynamic processes in the "soil-pipe-gas" system allowed us to define the patterns of propagation and decay of deformation waves. In the field tests, the emphasis was placed on studying the dynamic response of the pipeline to a number of external actions, such the action of the impact force on the pipe wall and soil in the vicinity of the pipe and gas pressure surges caused by the operation of shut-off valves. Comparison between the results of numerical and field experiments demonstrates the reliability of mathematical modeling. The obtained results can be used for designing new automated gas pipeline monitoring systems. The information obtained allows us to determine the structure of the monitoring system, evaluate the sensitivity of the sensors to various factors and obtain data for verification of the mathematical model describing the vibration processes in a gas pipeline.